2004
DOI: 10.1093/gerona/59.1.b3
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Effect of Dietary Restriction on Life Span and Mortality Rates in Female and Male Drosophila Melanogaster

Abstract: Dietary restriction (DR) has been shown to increase life span in taxonomically diverse animal species. In this study we tested for sex differences in the response of life span to graded severity of DR in Drosophila melanogaster. In both sexes, life span peaked at an intermediate food concentration and declined on either side. However, the magnitude of the response and the food concentration that minimized adult mortality differed significantly between the sexes. Female life span peaked at a food concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
202
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(230 citation statements)
references
References 42 publications
21
202
7
Order By: Relevance
“…Demographic modeling has suggested that dietary restriction in Drosophila acts by lowering age independent mortality rather than by slowing the accumulation of senescent damage (Mair et al 2003;Magwere et al 2004;Partridge et al 2005). In the present study, we did not observe such an effect.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Demographic modeling has suggested that dietary restriction in Drosophila acts by lowering age independent mortality rather than by slowing the accumulation of senescent damage (Mair et al 2003;Magwere et al 2004;Partridge et al 2005). In the present study, we did not observe such an effect.…”
Section: Discussioncontrasting
confidence: 88%
“…This observed longevity is particularly impressive because non-virgin females of the present study would be expected to have shorter lifespans than those reported previously for virgin females, due to the cost of reproduction (Chapman et al 1998). The full impact of these defined media on longevity in relation to fecundity in both female and males remains to be explored (Good and Tatar 2001;Magwere et al 2004).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Under laboratory settings, the lifespan of D. melanogaster has been successfully increased by genetic manipulations (Clancy et al., 2001; Hwangbo, Gershman, Tu, Palmer & Tatar, 2004; Kapahi et al., 2004; Lin, Seroude & Benzer, 1998; Orr & Sohal, 1994; Parkes et al., 1998; Sun, Folk, Bradley & Tower, 2002; Tatar et al., 2001), dietary interventions (Chapman & Partridge, 1996; Grandison, Piper & Partridge, 2009; Lee et al., 2014; Magwere, Chapman & Partridge, 2004; Mair, Goymer, Pletcher & Partridge, 2003; Min & Tatar, 2006), and pharmacological treatments (Bjedov et al., 2010; Danilov et al., 2013; Wang et al., 2013). These findings are similar to those reported in other model organisms and highlight the important role of nutrient sensing, mTOR, NAD/sirtuins, insulin/IGF1 signaling pathways, and other systems in lifespan control (Fontana, Partridge & Longo, 2010; He et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cohorts of female flies were selected for investigation, since DR has a much more substantial effect on lifespan in females than in males (Magwere et al 2004). An initial, control cohort (25/2SY) was cultured under normal conditions (25°C and 2SY food), to generate samples to optimise analytical methods and survey the chemical changes occurring during normal aging in D. melanogaster.…”
Section: Drosophila Melanogaster Culture Maintenance and Samplingmentioning
confidence: 99%